Датчик для измерения токов наносекундного диапазона на основе индукционного преобразователя - Шаламов, Станислав Павлович (НТУ "ХПИ", 2016)
Представлены результаты реализации высокочувствительного датчика токов наносекундного диапазона индукционного типа для измерения импульсов тока, протекающих на стержневом молниеприемнике. Проведен анализ современных достижений в области измерений слабых импульсных токов. Представлены результаты расчета датчика, показано влияние паразитных параметров на вид переходной характеристики датчика. Описаны основные особенности конструкции. Приведены параметры созданного датчика и результаты калибровки.

Purpose. A current meter based on the principle of electromagnetic induction is designed to register the current flowing in the rod lightning. The aim of the article is to describe the way of increasing the sensitivity of the converter by means of their serial communication. Methodology. The recorded current is in the nanosecond range. If compared with other methods, meters based on the principle of electromagnetic induction have several advantages, such as simplicity of construction, reliability, low cost, no need in a power source, relatively high sensitivity. Creation of such a meter is necessary, because in some cases there is no possibility to use a shunt. Transient properties of a meter are determined by the number of turns and the constant of integration. Sensitivity is determined by measuring the number of turns, the coil sectional area, the core material and the integration constant. For measuring the magnetic field pulses with a rise time of 5 ns to 50 ns a meter has turns from 5 to 15. The sensitivity of such a meter is low. When the number of turns is increased, the output signal and the front increase. Earlier described dependencies were used to select the main parameters of the converter. It was based on generally accepted and widely known equivalent circuit. The experience of created earlier pulse magnetic field meters was considered both for measuring the magnetic fields, and large pulse current. Originality. Series connection of converters has the property of a long line. The level of the transient response of the meter is calculated. The influence of parasitic parameters on the type of meter transient response is examined. The shown construction was not previously described. Practical value. The results of meter implementation are given. The design peculiarities of the given measuring instruments are shown.
An induction sensor for measuring currents of nanosecond range
Keywords: напряженность магнитного поля; ток короны; переходная характеристика; электромагнитная индукция; биэкспоненциальный импульс; калибровки индукционного преобразователя; линия с распределенными параметрами; magnetic field strength; corona current; surge characteristic; electromagnetic induction; bi-exponential pulse; induction transformer’s calibration; distributed parameter line